Revisiting the effects of molybdenum and tungsten alloying on corrosion behavior of nickel-chromium alloys in aqueous corrosion. Issue 3 (June 2019) - Lutton Cwalina, K.; Demarest, C.R.; Gerard, A.Y.; Scully, J.R.
Highlights: Minor alloying concentrations of Mo and W have major impacts on corrosion resistance. Mo and W influence affect all stages of passivation: growth, breakdown, and repassivation. Preferential Cr oxidation near Mo has been shown by theoretical and experimental results. Solute capture of Mo and W cations impacts point defect transport and passivation kinetics. Abstract: Minor alloying additions such as molybdenum (Mo) have major effects on the localized corrosion resistance of corrosion resistant alloys containing chromium. However, progress in alloy development is mostly based upon empirical observations, where any mechanistic insights are largely relegated to the latter stages of localized corrosion (i.e., stabilization and propagation) that are more readily accessible experimentally. For instance, it is well understood that Mo and tungsten (W) affect repassivation of local active, as well as widespread transpassive, corrosion sites and Mo surface enrichment during corrosion is well-documented. In this paper, a comprehensive examination of the functions and mechanism by which selected Mo and W operate to improve the passivity and resistance to breakdown during the initial stages of localized corrosion of the most common Ni-based solid solution alloys is presented. It is shown that Mo and W exert considerable influence on many stages of corrosion, including both passivation and film breakdown, re-enforcing old and introducing more recent ideas in this comprehensive review of the current state of corrosion research on Ni-Cr-(Mo + W) alloys.